Novel AlInN/GaN integrated circuits operating up to 500 °C. (November 2015) - Gaska, R.; Gaevski, M.; Jain, R.; Deng, J.; Islam, M.; Simin, G.; Shur, M.
Abstract: High electron concentration in 2DEG channel of AlInN/GaN devices is remarkably stable over a broad temperature range, enabling device operation above 500 °C. The developed IC technology is based on three key elements: (1) exceptional quality AlInN/GaN heterostructure with very high carrier concentration and mobility enables IC fast operation in a broad temperature range; (2) heterostructure field effect transistor approach t provides fully planar IC structure which is easy to scale and to combine with the other high temperature electronic components; (3) fabrication advancements including novel metallization scheme and high-K passivation/gate dielectrics enable high temperature operation. The feasibility of the developed technology was confirmed by fabrication and testing of the high temperature inverter and differential amplifier ICs using AlInN/GaN heterostructures. The developed ICs showed stable performance with unit-gain bandwidth above 1 MHz and internal response time 45 ns at temperatures as high as 500 °C.